Pelvic Gastrointestinal Stromal Tumor With Pulmonary Metastasis. Issue 8 (29th August 2019) - Akolkar, Shalaka; Melitas, Constantine; Piper, Marc
ABSTRACT: Extragastrointestinal stromal tumors (EGISTs) comprise a small portion of gastrointestinal stromal tumors. Metastasis normally occurs to nearby organs. However, metastasis to the lungs is uncommon in EGISTs. Furthermore, recurrence of the EGIST in a new location years later has not been documented. We present this case to highlight this behavior of EGISTs in hopes to better understand this rare type of neoplasm.